Pengembangan Media Pembelajaran Matematika Berbasis Aplikasi Android Menggunakan I-Spring Pada Materi Sistem Persamaan Linear Dua Variabel Kelas VIII SMP Negeri 4 Rote Barat Laut - Fanggi, Lerianto Yacob (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2025)
This research aims to develop mathematics learning media based on an Android application using I-Spring on two-variable linear equation systems material for class VIII students of SMP Negeri 4 Rote Barat Laut that is valid, practical and effective. The method used in this research is the Research and Development method using the ADDIE model. The data collection techniques and instruments used were interviews, questionnaires and tests. The data analysis techniques used are qualitative and quantitative data analysis techniques. The research results show that the learning media developed meets the eligibility criteria for learning media, namely valid, practical and effective. The average total validity by material and media experts was 4.41 in the "valid" category. The average total practicality of students in small classes is 4.615, the average total practicality of teachers in large classes is 4.67, and the average total practicality of students in large classes is 4.68 in the "practical" category. The percentage of student learning completeness in the small class trial was 100% with the "very effective" category and the large class trial was 75% with the "effective" category. Thus, the learning media developed is valid, practical and effective.